Chemical, dielectric and structural characterization of optimized hydrochar produced from hydrothermal carbonization of palm shell. (1st January 2016) - Nizamuddin, Sabzoi; Mubarak, N.M.; Tiripathi, Manoj; Jayakumar, N.S.; Sahu, J.N.; Ganesan, P.
Highlights: Hydrochar production from hydrothermal carbonization of palm shell is optimized. Temperature is found to be most effective parameter. Dielectric properties are temperature dependent. The surface characteristics of the hydrochar was much improved. Abstract: This paper primarily investigates the possible optimum conditions for maximum yield production of hydrochar through hydrothermal carbonization of palm shell. The hydrochar and the palm shell have been characterized to understand the effect of hydrothermal carbonization on palm shell and the chemical, the dielectric, and the structural properties of optimized hydrochar were examined. The effect of the reaction temperature, reaction time and biomass to water ratio was analyzed and optimized using the central composite design of response surface methodology. The optimized conditions for hydrochar production have been found to be 180 °C, 30 min, and 1.60 wt.%, temperature, time and biomass to water ratio, respectively. The findings showed that the temperature has a greater influence over the efficiency of hydrochar production than time and biomass-to-water ratio. The porosity of raw palm shell increased remarkably through hydrothermal carbonization. The dielectric constant of palm shell and hydrochar was decreased with an increase in frequency.